Back Cover: Toward Fully‐Fledged Quantum and Classical Communication Over Deployed Fiber with Up‐Conversion Module (Adv. Quantum Technol. 7/2021). Issue 7 (11th July 2021) - Bacco, Davide; Vagniluca, Ilaria; Cozzolino, Daniele; Friis, Søren M. M.; Høgstedt, Lasse; Giudice, Andrea; Calonico, Davide; Cataliotti, Francesco Saverio; Rottwitt, Karsten; Zavatta, Alessandro
Abstract : Future quantum networks will be able to share quantum and classical light within the same infrastructure by using different multiplexing methods, e.g., wavelength division multiplexing. In article number 2000156, Davide Bacco and co‐workers report how multiple signals (classical and quantum) are injected into a single‐mode fiber, showing the compliance of quantum technology with standard telecommunication networks.